The Family Physician: Teacher or Technocrat? - Gall, J. M. (1980)
With all the technological advances in medicine, something is still missing—doctors' responsiveness to patients' total health needs. Studies have shown that patients react more to the way in which they are treated than to the treatment itself. Physicians are often blinded by technology to the true root of a patient's problem. Their training needs more emphasis on individual and family dynamics, rather than on disease.